Inclusion in social innovation through the primary and secondary use of technology: a conceptual framework - Oomens, I. M. F.; Scholten, C. (International Review of Applied Economics, 2020)
People with disabilities are an important actor and target group in social innovation initiatives worldwide, as there is a clear need for better inclusion of this group in society. A way to improve the inclusion of people with disabilities is the development of assistive technology. In practice, people with disabilities often use technologies of which the primary use is not that of an assistive technology. They use the technology for a different use and context than the developer intended – termed 'secondary use'. The current paper studies the factors that are needed to make the secondary use of technology a success. First, a literature review and explorative study in the Netherlands are performed, after which a framework on the secondary use of technology for inclusion, specifically for people with disabilities, is developed.
Number: 5
Keywords: EDI; Europe; Personnes en situation de handicap; Réservé UdeM